Primary school teachers’ competences in constructing quality multiple-choice questions in Tanzania - Kyaruzi, Florence; Kisamo, Kingtin (International Journal of Evaluation and Research in Education (IJERE), 2025)
Multiple-choice questions (MCQs) are highly used in assessing students’ learning outcomes due to their versatility in promoting test content validity. Nevertheless, teachers experience psychometric challenges in constructing quality MCQs. This study investigated primary school teachers’ competence in constructing quality MCQs in Dar es Salaam Region, Tanzania. Specifically, we examined teachers’ competence in constructing quality MCQs, analyzed the types of item-writing flaws (IWFs) found in teacher-made MCQs, and examined the challenges that teachers encounter in constructing quality MCQs. The study was guided the by classical test theory (CTT) and it employed a mixed-method research approach. In particular, data collection and analysis were conducted using a concurrent triangulation design. A total of 213 MCQs constructed by 20 teachers from ten primary schools were collected and analyzed. The results indicated that primary school teachers were less competent in constructing quality MCQs as 156 (73.2%) of the teacher-made MCQs assessed lower levels of Bloom’s cognitive domain. Similarly, most of the MCQs had IWFs, with 274 (69.2%) having test wiseness flaws and 122 (30.8%) having irrelevant difficulty flaws. The findings call for capacity building to promote teachers’ competence in constructing quality test items.